The relationships between relative age effect, personality constructs and achievement level in soccer - Bolckmans, Sofie; Perquy, Kris; Starkes, Janet L.; Memmert, Daniel; Helsen, Werner F. (Frontiers in Sports and Active Living, 2023)
young players developing superior psychological skills and technical expertise to compensate for their early physical disadvantage. This in turn suggests the need for greater awareness of the importance of personality constructs in the future development of youth elite soccer players. Therefore, the crux of the issue is how youth soccer academies elicit the 'best of both worlds' ie. moderating RAE whilst also gaining the benefits of the underdog hypothesis by creating the right environment for every player to develop to their full potential in elite youth soccer academies.